Reformasi Pondok Pesantren Dan Pendidikan Multikultural - Nasrul Nasrul; Iswantir M; Zulmuqim Zulmuqim (Neolectura, 2022)
Islamic Boarding School education, in general, has not shown satisfactory results, based on stakeholder expectations. The existing Islamic Boarding School education system still requires serious studies to move towards better improvements. Reform of Islamic education, especially Islamic boarding schools, is an urgent demand because generations are faced with various multidimensional challenges of life. The role of pesantren as a means of education and socialization has its own meaning for its students as a place to seek knowledge and experience as well as a place to make friends and interact socially. During the period of study and socialization, students will meet a group of friends with very different personalities and habits. Therefore, the integration of multicultural values ??in Islamic boarding school learning can be an alternative model of multicultural education in society. Because the essence of multicultural education is not to implement the nomenclature of multicultural learning, but to realize the internalization of these multicultural values ??in people's lives constructed by pesantren. This research study aims to describe the reform of Islamic boarding schools and multicultural education. This type of research is library research, focusing on discussing literature in the form of books, journals, papers, and other writings, with a qualitative approach. In addition, the author also uses an interpretation method in order to achieve a correct understanding of Islamic boarding schools and multicultural education.